Monetary Stability Challenges characterising the European Integration Process of the Republic of Moldova - Dorina Clichici; Andreea - Emanuela Drăgoi; Tatiana Covalschi (Romanian Journal of European Affairs, 2025)
For more than 20 years, the Republic of Moldova has been carrying out a multitude of economic reforms aimed at getting closer to the European Union (EU). Despite the remarkable results culminating in the status of EU candidate country, the Moldovan economy continues to struggle with a high vulnerability to internal and external shocks, which generates major fluctuations in prices and in the exchange rate. This volatility greatly affects the macroeconomic stability, undermining the national objective of economic growth and, ultimately, the efforts to increase economic convergence with the EU. Against this background, the paper aims to identify the main challenges to monetary stability in the Republic of Moldova since the signing of the Association Agreement with the EU, and to uncover the ways in which monetary policy has so far dealt with major shocks. Moreover, it aims to analyse the degree of convergence with the EU regarding price and exchange rate stability of the Republic of Moldova over the last ten years. The findings highlight that the National Bank of Moldova (NBM) managed to restore monetary stability thanks to its prompt and large-scale actions. However, significant convergence gaps in terms of price stability do persist between the Republic of Moldova and the EU.